'Taman Keceh' Tourism Development Training as a Means of Public Education For the People Around Celaket - R. Anggia Listyaningrum; M. Ishaq; Lasi Purwito; Edi Widianto (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Taman Keceh is one of the new attractions in the Samaan area of Celaket area of Malang City which is considered very useful for the surrounding residents. Beyond the existing utilization, the utilization of Taman Keceh tourist attractions can also be optimized as a public education center. Community service activities carried out are training-based activities, namely training in the development of Taman Keceh Tourism as a means of public education for the surrounding community. This activity aims to equip the manager of Taman Keceh Tourism with skills, not just understanding and knowledge, related to knowledge and practice in managing informal learning activities for the community and visitors to Taman Keceh. The methods used in this activity include methods of deliberation, brainstorming, demonstration, and practice. In the process, the manager/manager of the organization is accompanied by sources and a team of service implementers as facilitators of activities. Evaluations include evaluations before, during, and after training activities. The results obtained from this devotional activity include priority problems and needs of the target community as a basis for the preparation of activity plans, increasing understanding, awareness, and skills of managers and residents around Keceh Park to the importance of public education in their environment, as well as the results of the evaluation of activities that show supporting factors and activities inhibition factors so that they can be used as material for the improvement of further activities.